Penafsiran Ayat Al-Qur'an Tentang Kesaksian Seorang Lelaki dan Dua Perempuan Dalam Tinjauan Maqashid Shariah - Latif, Hamdiah (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2020)
This article would like to discuss about the meaning of equality on the verse of Al-Qurâ€Ÿan (Al-Baqarah: 282): â€œone man two womenâ€ in terms of testimony. However, various interpretations have broadly attracted the attention of many interpreters of the Al-Qur'an dealing with the meaning of justice and equality between man and woman. By using Maqashid Shariah as the tool of analysis, this article would like to elaborate more on finding the purposes of sharia by stating that one man equal two women regarding testimony. The main problem is what the verse should be interpreted looks like: whether literally or trying to find the depth meaning by searching the purposes of sharia behind the meaning of justice and equality in terms of testimony of man and woman. Besides, finding the purposes of sharia's view on the issue of gender equality which is increasingly debated in the current contemporary times becomes more important in order to get its comprehensive view on such matter.Â Â Â Â Â